PENINGKATAN PEMAHAMAN KONTRIBUSI TEORITIS BAGI PENELITI PEMULA BIDANG MANAJEMEN DAN BISNIS DI PERGURUAN TINGGI ABC - Muhammad Rasyid Abdillah; Adi Rahmat; Suhardiman Hamby; Rizqa Anita; Liza Rizqi (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2026)
This community service activity aims to enhance novice researchers’ understanding of theoretical contribution in the fields of management and business at Perguruan Tinggi ABC. The main problem faced by the participants is limited conceptual understanding of the meaning and forms of theoretical contribution in scientific research, which often results in weak articulation of theoretical contribution in academic articles. The activity was conducted through a face-to-face workshop designed to strengthen both conceptual and practical understanding of theoretical contribution in research. A total of ten early-career researchers from management and business disciplines participated in the program. The effectiveness of the activity was evaluated using a pretest–posttest approach to measure changes in participants’ understanding before and after the training. The pretest results indicated that most participants were unable to adequately explain theoretical contribution from a scientific perspective. However, the posttest results, based on case analysis, showed a clear improvement in participants’ ability to identify and formulate theoretical contributions in research. These findings suggest that the training activity was effective in improving novice researchers’ conceptual understanding of theoretical contribution and has the potential to support the improvement of research quality and academic publications within Perguruan Tinggi ABC. Keywords: research theoretical contribution; early-career researchers; management and business, training, community service